Impact of Radial Bowing Alteration on Functional Outcomes Following Locked Intramedullary Nailing of Adult Both-Bone Forearm Fractures - Tütüncü, Mehmed Nuri; Sevgin, Muhammed Muvahhid; Akbulut, Salim Çağatay; Akpinar, Fuat (The European Research Journal, 2026)
Objectives: Plate osteosynthesis is the standard treatment for adult both-bone forearm fractures, but locked intramedullary nailing (IMN) offers a minimally invasive alternative. Its impact on restoring radial bow and functional outcomes is unclear. This study assessed changes in radial bow magnitude and location after IMN and their relationship with functional outcomes. Methods: Twenty-six adult patients who underwent locked IMN for diaphyseal both-bone forearm fractures between 2015 and 2024 were retrospectively analyzed. Demographic data, radiographic measurements, union time, functional scores, and range of motion were recorded. Radial bow magnitude and bow apex location were measured on standardized radiographs and compared between the operated and contralateral forearms. Correlation analyses were performed to evaluate associations between bow changes and functional outcomes. Results: All fractures achieved union, with no cases of nonunion or radioulnar synostosis. The mean time of union was 10.7±1.8 weeks. Extensor pollicis longus (EPL) rupture occurred in two (7.7%) patients. Postoperative radiographs showed reduced bow magnitude (Δ=0.61±1.13 mm; P=0.010) and a distal shift in bow location (Δ = –5.38±5.39%; P=0.001) on the operated side. A significant negative correlation was found between distal bow displacement and supination (r = –0.561; P=0.003). No correlation was observed with pronation, VAS, or QuickDASH scores. Conclusions: Locked IMN ensures reliable union and excellent function. While IMN changes radial bowing, only excessive distal displacement impairs supination.